Refocusing development towards sustainability – the case of Selangor, Malaysia - Joy Jacqueline Pereira,; Ibrahim Komoo,; Mohd Nordin Hasan,; Halimaton Saadiah Hashim, (Environmental Management Society, Malaysia, 2005)
Local Agenda 21 offers a holistic approach to incorporate sustainability in local policies across all sectors, with the involvement of the community. Local Agenda 21 initiatives focused on the local authority level, as this was deemed to be the level closest to the community. The bottom-up approach was promoted whereby local authorities worked in partnership with non-governmental organisations and other stakeholders. This approach is not particularly suited for the State of Selangor, Malaysia. Instead, the state government opted for an innovative and comprehensive approach, combining both the “top-down” and “bottom-up” approaches, modified for the existing three tiered governance mechanism. In this approach, principles, strategies and strategic action plans were formulated at the state level with the participation of all stakeholders. These were then channeled directly to various agencies involved in policy-making, planning and implementation. These agencies, in particular the state agencies, federal agencies operating in the state and local authorities, then become jointly responsible for formulating and implementing programmes, projects and activities related to sustainable development, in conjunction with all stakeholders. The agencies are also required to formally report the progress of their initiatives to the state. It is unrealistic to anticipate a total positive response in the initiative to implement Agenda 21 Selangor, where every stakeholder whether an individual, agency or organisation, would progress forward in harmony and at the same speed. But with top-level commitment and a high level of engagement from all stakeholders, the shift towards sustainbility has commenced. Notwithstanding this, long term success depends on the provision of clear policy and adequate resources, strengthening of the planning system and capacity to make multi-sectoral and integrated decisions